Analisa Kelayakan Pembelian Mesin Packaging 1Kg pada PT. X Berdasarkan Aspek Teknis, Lingkungan Kerja, dan Finansial - David Suhendra; Benedictus Rahardjo (Jurnal Titra, 2018)
The purpose of this research is to analyze the feasibility of buying a packaging machine 1kg that will be done by PT. X. The analysis includes three aspect that is technical, work environment and financial. The analysis of technical aspect will be choosing which machine should PT. X buy, the analysis of this aspect using value assessment methods. There are two machine offered with different specification, based on analysis machine A has better value than machine B therefore PT. X should buy machine A. The work environment aspect will be analyzed of social impact for workers compared to government regulations. In this research work environment element that used is noise, based on observation the work environment in PT. X is appropriate with government regulation. Financial aspect is analyzed with three methods that is NPV, IRR, and payback period. The result is NPV Rp. 58.882.595,86, with an IRR 37.67% and payback period 2.09 years. It is concluded that buying a packaging machine 1 kg at PT. X is feasible based on three aspect that has been assessed.